A modular telescope facility to investigate the cosmic ray decoherence curve. (5th August 2021) - Riggi, F.; La Rocca, P.; Pinto, C.; Riggi, S.
Abstract: This paper describes the use of a set of small cosmic ray detectors for the measurement of the decoherence curve, i.e. the probability of observing coincidence events between pairs of particles from an extensive air shower as a function of the separation distance between them. Individual detection modules were arranged into 15 telescopes located in various positions, such as to cover nominal separation distances between 0.5 and about 25 m with a fine mesh. A measurement of the decoherence curve has been carried out during a period of approximately 24 days at an altitude close to the sea level, with the detectors located in a large lecture hall of the Physics Department, below a concrete roof. Results were also compared to theoretical simulations of extensive air showers based on Corsika. Performance of the method is discussed, with possible extension of this technique to provide a low-cost facility for the investigation of the decoherence curve at even larger distances.